Use of the 2D:4D digit ratio as a biological marker of specific language disorders - Antònia Font-Jordà; Antoni Gamundí; María Cristina Nicolau Llobera; Eva Aguilar-Mediavilla (Anales de Pediatría (English Edition), 2018)
Introduction: The finding of biological markers of specific language impairment would facilitate their detection and early intervention. In this sense, the 2D:4D finger ratio is considered an indirect indicator of prenatal exposure to testosterone. Previous studies have related it to linguistic competence and aggressive behaviour, and could be a candidate for a biological marker of language impairment. The aim was to compare the value of the 2D:4D ratio in children with Specific Language Impairment (SLI) with those of children with typical language development, as well as to establish to what extent this biological index correlates with the behaviour (linguistic, cognitive, social,...) in both groups. Subjects and methods: 2D:4D ratio, language, cognition and social behaviour were compared in a group of children with SLI (n = 15), with a group of children without language difficulties (n = 16) of the same age (between 5 and 8 years), gender (male), and socio-cultural level. Results: Children with SLI showed significantly higher values of 2D:4D ratio of the right hand, and a negative correlation between this ratio and their linguistic competence. Although the children with SLI showed impaired adaptive abilities, but not more aggressive behaviour, these measurements did not correlate with the 2D:4D index. Nevertheless, social behaviour correlated with language and cognition competence. Conclusions: A higher value of the biological 2D:4D ration (lower intrauterine exposure to testosterone) seems to be associated with language difficulties in boys with SLI, but not with their behavioural difficulties. Their behavioural difficulties seem to be a consequence of their linguistic difficulties and their level of cognition. Resumen: Introducción: Encontrar marcadores biológicos del trastorno específico del lenguaje facilitaría su detección e intervención precoz. En este sentido, el índice digital D2:D4 es considerado un indicador indirecto de la exposición prenatal a la testosterona, y estudios previos lo han relacionado con la competencia lingüística y la conducta agresiva, por lo que podría ser un candidato a marcador biológico. El objetivo es comparar el valour de este índice digital en niños con trastorno específico del lenguaje (TEL) frente a sujetos con desarrollo típico del lenguaje, estableciendo en qué medida correlacionan los valores del índice biológico con la conducta (lingüística, cognitiva, social…) de dichos sujetos. Sujetos y métodos: Se comparó el índice D2:D4, el lenguaje, la cognición y la conducta social en un grupo de niños con TEL (n = 15) con un grupo de niños sin dificultades del lenguaje (n = 16) de la misma la misma edad (entre 5–8 años), sexo (masculino) y nivel sociocultural. Resultados: Los niños con TEL mostraron valores significativamente más altos en el índice D2:D4 de la mano derecha, y una correlación negativa entre el índice D2:D4 de la mano derecha y la competencia lingüística. Aunque los niños con TEL mostraron peores habilidades adaptativas y conductas internalizantes, aunque no mayor agresividad, estas medidas no se correlacionaron con el índice D2:D4, y sí con los valores de lenguaje y de cognición. Conclusiones: Un valour más alto del índice biológico D2:D4 (menor exposición intrauterina a la testosterona) parece estar asociado con las dificultades del lenguaje de los niños con TEL, pero no con sus dificultades conductuales. Las dificultades conductuales de estos niños parecen ser consecuencia de sus dificultades lingüísticas y de su nivel de cognición.